Risk Perception of Rural Land Supply Reform in China: From the Perspective of Stakeholders - Zhongqiong Qu; Yongxin Wei; Xun Li (Agriculture, 2021)
The reform of rural land supply market has a profound impact on the rural management and agricultural development. In this article, we want to explore risk perception of multi-subject land supply reform in China. The perception of potential risks from the perspective of stakeholders can evaluate the effect of a certain behavioral decision and provide a convincing explanation for further risk control. Based on theoretical analysis and practical investigation, we define the five stakeholders, namely collective economic organizations, farmers, local government, banks and land users, as the respondents of our questionnaire survey. Through in-depth interviews and literature review, we obtained the categories of risks with stakeholders. Data were obtained through questionnaire survey, a total of 307 surveys were conducted to analyze the probability of risk occurrence and the severity of consequences. Frequency analysis, risk matrix method, and Borda count method were used to analyze the survey results in order to determine the risk level and key risk. The research finds that the information asymmetry risk perceived by farmers and the market risk perceived by banks are key risks. In terms of stakeholders, famers and banks perceived the highest overall risks. It implies that the information-disadvantaged stakeholder is usually the one with a strong sense of risk.